Effect of Magnetic Field on some Physical Properties of Tap Water (Global Journal of Science Frontier Research, 2018)
Passing water through a magnetic flux has been claimed to boost chemical, physical and medicinal quality of water in many alternative applications. Though, the treatment method has been used for many years, it still remains within the realms of fallacy. If the claims of treating water with magnets are a unit true, the method offers enhancements on several of our applications of water in today's world. A big range of peer-reviewed journal articles have according contradictory claims concerning the treatment. A number of the foremost useful claimed water applications from magnetically treated water embody improvement in scale reduction in pipes and increased crop yields with reduced water usage. However, we are still unsure whether or not the technology works and researchers do believe it works and are still attempting to know the mechanisms of how it works. Several analysis papers are setting out to develop similar theories behind the mechanism of the treatment. The majority of the experiments performed throughout this analysis were determined to own deficient controls to provide conclusive results. The conclusions from this analysis were centred on coming up with improved experiments to produce additional conclusive results.
Keywords: magnetic field; surface tension; conductivity; resistivity; electromagnet